2022
DOI: 10.1002/jez.2633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sugar cane extract on steroidogenesis in testicular interstitial cells of male Japanese quail (Coturnix japonica)

Abstract: Sugar cane extract (SCE) is the end product of glucose, fructose, and sucrose elimination in molasses. SCE has various biological effects, such as anti-inflammation and antioxidation, and it is commonly found in animal feed. The present research is aimed at investigating the reproductive endocrine influence of SCE in male Japanese quails (Coturnix japonica) by feeding SCE containing food. In addition, in vitro Leydig cell culture was conducted to clarify the mechanism of SCE's influence. Our results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…was carried out on male quail after supplementing their feed with an extract derived from sugarcane molasses, where the effects of reproductive endocrine activity was evaluated. The study reported a decrease in serum testosterone, and testicular and epidydimal weight, an inhibition of hydroxysteroid dehydrogenase and suppressed sexual behaviour, suggesting the ability of sugarcane molasses supplementation on impeding steroidogenesis (Pu et al, 2022). The authors concluded that this was useful in the poultry industry in managing livestock, as decreased testosterone leads to efficient feed to growth conversion, as well as contributing to improved quality of meat (Rikimaru et al, 2009).…”
Section: Impact On Animal Growth Performancementioning
confidence: 97%
See 1 more Smart Citation
“…was carried out on male quail after supplementing their feed with an extract derived from sugarcane molasses, where the effects of reproductive endocrine activity was evaluated. The study reported a decrease in serum testosterone, and testicular and epidydimal weight, an inhibition of hydroxysteroid dehydrogenase and suppressed sexual behaviour, suggesting the ability of sugarcane molasses supplementation on impeding steroidogenesis (Pu et al, 2022). The authors concluded that this was useful in the poultry industry in managing livestock, as decreased testosterone leads to efficient feed to growth conversion, as well as contributing to improved quality of meat (Rikimaru et al, 2009).…”
Section: Impact On Animal Growth Performancementioning
confidence: 97%
“…Regarding animal performance, a study by Pu et al (2022). was carried out on male quail after supplementing their feed with an extract derived from sugarcane molasses, where the effects of reproductive endocrine activity was evaluated.…”
Section: Impact On Animal Growth Performancementioning
confidence: 99%